Coach Justin’s Self-Identity Formation on Youtube Social Media: Pembentukan Identitas Diri Coach Justin di Media Sosial Youtube - Kurniawan, Galang Bagus; Adabi, Faizal Bakhron (Universitas Muhammadiyah Sidoarjo, 2025)
This study analyzes Coach Justin's self-identity formation as a professional football coach on YouTube social media. This qualitative research uses the content analysis method to understand how Coach Justin builds his identity through video content, comments and interactions with the audience. The results showed that Coach Justin succeeded in building an identity as a coach who is professional, inspiring and close to his audience through educational, motivational and interactive content. The research also found that Coach Justin uses effective communication strategies such as casual language, humor and analogies to convey complex football messages. In addition, interaction with the audience through comments and live streaming also strengthens Coach Justin's relationship with his followers. This research contributes to the understanding of the role of social media in self-identity formation and effective communication. The results can serve as a reference for coaches, influencers and other content creators to build effective self-identity on social media.